Pengabdian Masyarakat pada Pemilik Warung Makanan dalam Penyajian Makanan Halal - Tholib Hariono; Nur Khafidhoh; Siti Sufaidah; Munawaroh Munawaroh; Nurul Yaqin (LPPM Universitas KH. A. Wahab Hasbullah, 2022)
Banjarsari Village for some people around Jombang is also a sought-after village for a tour because it still presents a beautiful rural atmosphere and panorama. This opportunity for some people is used to open a simple shop to make a profit, therefore there are many food stalls that serve a variety of food menus. However, most people do not understand about halal standards in the food production process. Often people ignore the cleanliness and halalness of the products served. The purpose of this service is to provide education and direction to several food stall managers so that they always maintain the process of cleanliness, health, purity and halalness. The guarantee of product halalness in the management of food stalls is an effort to ensure the appropriateness of the standards of food sold to consumers that are really hygienic, clean and healthy as well as halal. The activity, which was held with the UNWAHA Islamic Center in Banjarsari Village, was carried out very well and received high enthusiasm from the food stall owners. The result of this activity is that the shop owner gains an understanding of how to cook and manage healthy food and according to Islamic law. Shop owners who have participated in this activity put stickers on their respective stalls as evidence that they have understood the importance of health and compliance with Islamic law in cooking and serving patterns. Providing a clear price list and according to general standards is also one of the training materials.